The discovery of the virulence gene ToxA in the wheat and barley pathogen Bipolaris sorokiniana. (12th March 2017) - McDonald, Megan C.; Ahren, Dag; Simpfendorfer, Steven; Milgate, Andrew; Solomon, Peter S.
Summary: Bipolaris sorokiniana is the causal agent of multiple diseases on wheat and barley and is the primary constraint to cereal production throughout South Asia. Despite its significance, the molecular basis of disease is poorly understood. To address this, the genomes of three Australian isolates of B. sorokiniana were sequenced and screened for known pathogenicity genes. Sequence analysis revealed that the isolate BRIP10943 harboured the ToxA gene, which has been associated previously with disease in the wheat pathogens Parastagonospora nodorum and Pyrenophora tritici‐repentis . Analysis of the regions flanking ToxA within B. sorokiniana revealed that it was embedded within a 12‐kb genomic element nearly identical to the corresponding regions in P. nodorum and P. tritici‐repentis . A screen of 35 Australian B. sorokiniana isolates confirmed that ToxA was present in 12 isolates. Sequencing of the ToxA genes within these isolates revealed two haplotypes, which differed by a single non‐synonymous nucleotide substitution. Pathogenicity assays showed that a B. sorokiniana isolate harbouring ToxA was more virulent on wheat lines that contained the sensitivity gene when compared with a non‐ ToxA isolate. This work demonstrates that proteins that confer host‐specific virulence can be horizontally acquired across multiple species. This acquisition can dramatically increase the virulence of pathogenic strains on susceptible cultivars, which, in an agricultural setting, can have devastating economic and social impacts.